Micronutrient Status Across Pregnancy in Women with Overweight and Obesity (P11-008-19). (13th June 2019) - Gernand, Alison; Taylor, Leigh; Hohman, Emily; McNitt, Katherine; Downs, Danielle Symons; Savage, Jennifer
Abstract: Objectives: To describe changes in maternal micronutrient status between the first and third trimesters and examine differences by obesity status. Methods: Pregnant women were recruited between 8 and 12 weeks gestation as part of the Healthy Mom Zone study. Participants provided a blood sample at enrollment and at approximately 36 weeks (n = 30). Five micronutrients (iron, zinc, copper, vitamin A, and vitamin D) were examined using 14 measured biomarkers at both time points; ferritin, zinc, and retinol were adjusted by markers of inflammation. Iron biomarkers (serum iron, ferritin, total iron binding capacity, and transferrin receptor) were measured by ELISA. Zinc and copper were measured by flame atomic absorption spectroscopy, retinol by UPLC, and 25-hydroxyvitamin D (and the C-3 epimer) by HPLC tandem mass spectrometry. Results: Most women were nulliparous (64%) and all women reported taking a prenatal supplement. Mean (SD) age was 30.5 (3.0) years. Thirty-six % of women were classified as overweight and 50% as obese prepregnancy. Infant birth weight was 3407 (575) grams and only one infant was born preterm. In the first trimester, few women had micronutrient deficiencies: 2 women were iron deficient (1 with anemia) and 0 women were deficient in zinc, copper, vitamin A or vitamin D. By the third trimester, 10 women (33%) were iron deficient and 10 were zinc deficient; 4 women (13%) had co-occurring iron and zinc deficiencies. Three women were anemic (without iron deficiency) at the second measurement. Most biomarker concentrations changed significantly from first to third trimester (Table); on average, ferritin, zinc, and retinol decreased while copper and 25-hydroxyvitamin D increased (all P  < 0.05). Serum iron, transferrin saturation, and hematocrit remained relatively constant. However, there were large individual differences; some women increased and other women decreased for most biomarkers. Prepregnancy obesity was not related to micronutrient status at either time point. Conclusions: In a sample of pregnant women in which half had obesity, iron and zinc deficiencies were common in the third trimester in spite of supplementation beginning in early pregnancy. Biomarkers changed from first to third trimester for all 5 micronutrients examined, yet status was not related to prepregnancy obesity. Funding Sources: NIH NHLBI. Supporting Tables, Images and/or Graphs: